Implementation of Halal Certification Institutions in ASEAN Countries - Sholihah, Fefi Diniyati; Arifin, Sirajul (Journal of Islamic Economic Scholar, 2025)
ASEAN serves as an integrated market and manufacturing hub, facilitating the seamless movement of goods, services, capital, investment and production . Wrong One regulation Which applied rates customs enter Which imposed on goods Which traded in between countries ASEAN members . Implementation trading free in ASEAN cause concerns among​ public Muslim in Indonesia And countries ASEAN other regarding the halal status of imported products. To overcome this problem, standardized requirements, labels, and registration procedures are needed for halal certification. This study aims to analyze the implementation of halal certification in halal certification institutions in ASEAN countries, especially Indonesia, Malaysia, and Thailand. This study uses comparative qualitative by collecting primary and secondary data. Primary data is obtained from information on official government websites and halal certification institutions. Meanwhile, secondary data is obtained from literature such as journals, articles, and books that are relevant to the research topic. Such as the halal standards of each country and comparing them with aspects of technology, determination procedures, legal issues, and audit methods. The results of the analysis show that ASEAN member countries, especially Indonesia, Malaysia and Thailand, have different regulations and requirements for implementing halal assurance standards. However, these differences create confusion and hinder international trade. Say Key: ASEAN; Indonesia Malaysia Thailand; Certification halal; Halal standards